PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENGATASI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PADA SUB POKOK BAHASAN ARITMATIKA SOSIAL DI SMP NEGERI SATU ATAP TANGGUL KELAS VII B SEMESTER GANJIL TAHUN - Mukti, Dyna Probo; Susanto, S; Dafik, D (Department of Mathematics Education , University of Jember, 2012)
Abstract. Cooperative learning type Student Teams Achievement Divisions (STAD) is combination methods between cooperative learning and individual learning. In this research, we will implement STAD to reduce can minimalize student’s error in the topic of social arithmetic. The subject of the research is grade VII B students of SMP Negeri Satu Atap Tanggul. The data collection methods used in this research are test, interview, observation and documentation. The result shows that the errors are decreasing; theorem error decrease from 37,85% to 20,71%; data error decrease from 52,14% to 32,14%; technique error decrease from 42,85% to 24,28% and other error decrease from 39,28% to 18,57%. The result also shows that the teaching learning activity using STAD gives a good responses from the teacher and students. Key Words : STAD, student’s error, social arithmetics